2005
DOI: 10.1111/j.1540-8183.2005.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Stenosis: Epidemiology, Clinical Manifestation, and Percutaneous Endovascular Therapy

Abstract: Renal artery stenosis may cause or deteriorate arterial hypertension and/or renal insufficiency. Technical improvements of diagnostic and interventional endovascular tools have lead to a more widespread use of endoluminal renal artery revascularization and extension of the indications for this type of therapy. Since the first renal artery angioplasties performed by Felix Mahler and Andreas Grüntzig in 1978, numerous single-center studies have reported the beneficial effect of percutaneous transluminal renal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 115 publications
1
24
0
1
Order By: Relevance
“…However, RI does not predict outcomes after renal revascularization despite initial, promising results. 19 Although compliance of intrarenal arteries influences RI, changes in these vessels often reflect a similar process throughout the systemic vasculature that can be the result of altered central hemodynamics associated with aging. 13,20 Thus, differentiating the role of renovascular factors from the role of systemic vascular factors in the prognostic information provided by renal RI can be problematic.…”
mentioning
confidence: 99%
“…However, RI does not predict outcomes after renal revascularization despite initial, promising results. 19 Although compliance of intrarenal arteries influences RI, changes in these vessels often reflect a similar process throughout the systemic vasculature that can be the result of altered central hemodynamics associated with aging. 13,20 Thus, differentiating the role of renovascular factors from the role of systemic vascular factors in the prognostic information provided by renal RI can be problematic.…”
mentioning
confidence: 99%
“…Several previous studies demonstrated that a side-to-side difference in RRI of at least 0.05 is a specific marker of severe unilateral renal artery stenosis [35]. However, because of the major influence of the systemic hemodynamic factors and renal vascular compliance on the intrarenal arterial waveforms, the RRI could not serve as a specific marker reflecting exclusively renal artery resistance or renal pathology.…”
Section: Prognostic Significance Of the Rrimentioning
confidence: 90%
“…However, conventional angiography still has superior resolution for the evaluation of small vessels and offers the option of simultaneous therapeutic interventions such as percutaneous revascularization by balloon angioplasty and/or stenting. [11] Surgical intervention is often reserved for selected cases based mainly on the mapping of findings of the renal arteries.…”
Section: Introductionmentioning
confidence: 99%
“…[11] The aim of the present study is to compare these four imaging methods in a patient cohort suffering from hypertension attributed to renovascular etiology and suggest an imaging algorithm according to the imaging findings.…”
Section: Introductionmentioning
confidence: 99%